Effects of bergamot essential oil and its extractive fractions on SH-SY5Y human neuroblastoma cell growth. (24th March 2015) - Navarra, Michele; Ferlazzo, Nadia; Cirmi, Santa; Trapasso, Elena; Bramanti, Placido; Lombardo, Giovanni Enrico; Minciullo, Paola Lucia; Calapai, Gioacchino; Gangemi, Sebastiano
Abstract: Objectives: The goals were to investigate the mechanisms underlying the antiproliferative effects of bergamot essential oil (BEO) and to identify the compounds mainly responsible for its SH-SY5Y cells growth rate inhibition. Methods: Five BEO extractive fractions (BEOs) differing in their chemical composition were used. Cell proliferation was determined by 3-(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and cell count assays. Trypan blue exclusion test and Annexin V/PI staining were performed to assess their cytotoxic activity. Genotoxicity was detected by comet assay. The cell cycle was checked cytofluorimetrically. Reactive oxygen species (ROS) and Δψm were measured fluorimetrically. Western blotting analyses for some apoptosis-related proteins were carried out. Key findings: Treatment of SH-SY5Y cells with some types of BEOs decreased cell growth rate by a mechanism correlated to both apoptotic and necrotic cell death. Coloured BEOs act by increasing ROS generation, responsible for the drop in Δψm, and modulate p38 and extracellular signal-regulated kinases (ERK ½) mitogen-activated protein kinases, p53, Bcl-2 and Bax signalling pathways. Finally, we identify bergamottin and 5-geranyloxy-7-methoxycoumarin as the bioactive molecules that could play a pivotal role in the antiproliferative effects exerted by coloured BEOs. Conclusions: Our study provides novel insights into the field of the antiproliferative effects of BEO, which could be exploited in the context of a multitarget pharmacological strategy.